UTILIZATION OF PEOPLE'S BUSINESS CREDIT BY MSMES IN THE CONTEXT OF BUSINESS DEVELOPMENT IN THE COASTAL MARKET AREA, MALABERO VILLAGE - Ganefi; Nurhani Fithriah; Arjun Nanda Dagusto (Universitas Bengkulu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy by absorbing labor, creating jobs, and supporting economic growth, particularly in coastal market areas such as Malabero Village, Bengkulu City. This research aims to analyze the utilization of People’s Business Credit as a government-supported micro-credit program and its role in supporting business development among MSMEs in the coastal market area of Malabero Village. This research employed an empirical legal research approach using field data as the primary source, collected through interviews with MSME actors in the Malabero coastal market area. The findings indicate that the utilization of micro-credit remains relatively low, as only a small proportion of business actors have accessed the program, mainly those with higher capital needs, while limited information, low financial literacy, and fear of debt hinder wider participation. The research concludes that strengthening financial literacy, improving program socialization, and providing continuous assistance are essential to enhance effective micro-credit utilization and promote sustainable MSME development in coastal areas.